Pengaruh Penerapan Model PBL Terhadap Kemampuan Pemecahan Masalah Siswa di Sekolah Menengah - Wahyuni, Tri; Syutaridho, Syutaridho; Efriani, Arvin (Edumatica : Jurnal Pendidikan Matematika, 2023)
Problem-solving ability is an essential ability for all students to have. However, students still experience difficulties solving problems, so a learning model is needed to support students' problem-solving abilities. This research aims to determine the influence of applying the Problem-Based Learning (PBL) learning model on students' problem-solving abilities. The research method used is a quantitative method with a Posttest-Only Control Design. The population of this research is all 3 class VIII students, with a total of 69 students. The sample used was 2 classes with a total of 46 students. This research was carried out at An-Nuriyah Sekayu IT Middle School, September 12-October 04, 2023, using a quota sampling technique in which predetermined classes from the school were used as samples. The data collection technique used is test questions. Based on data analysis, a value of = 1.194965 and a value of Â = 2.015367574 so that it was obtained , then it causes it to be Â rejected and accepted. So, the conclusion is that the Problem Based Learning model influences the mathematical problem-solving abilities of class VIII students at SMP IT An-Nuriyah Sekayu.